In-Vitro Evaluation of the Antioxidant and Anti-Inflammatory Activity of Volatile Compounds and Minerals in Five Different Onion Varieties - Rokayya Sami; Abeer Elhakem; Mona Alharbi; Manal Almatrafi; Nada Benajiba; Taha Ahmed Mohamed; Mohammad Fikry; Mahmoud Helal (Separations, 2021)
Onions contain high antioxidants compounds that fight inflammation against many diseases. The purpose was to investigate some selected bioactive activities of onion varieties (Yellow, Red, Green, Leek, and Baby). Antioxidant assays and anti-inflammatory activities such as NO production with the addition of some bioactive components were determined and analyzed by using a spectrophotometer. Gas chromatography and mass spectrometry (GC–MS) was used for the volatile compounds, while an Atomic absorption spectrometer was used for mineral determinations. Red variety achieved the highest antioxidant activities. The total flavonoids were between (12.56 and 353.53 mg Quercetin/gin dry weight) (dw) and the total phenol was (8.75–25.73 mg/g dw). Leek, Yellow and Green extracts achieved highly anti-inflammatory values (3.71–4.01 μg/mL) followed by Red and Baby extracts, respectively. The highest contents of sodium, potassium, zinc, and calcium were established for Red onions. Furfuraldehyde, 5-Methyl-2-furfuraldehyde, 2-Methyl-2-pentenal, and 1-Propanethiol were the most predominant, followed by a minor abundance of the other compounds such as Dimethyl sulfide, Methyl allyl disulfide, Methyl-trans-propenyl-disulfide, and Methyl propyl disulfide. The results recommend that these varieties could act as sources of essential antioxidants and anti-inflammatories to decrease inflammation and oxidative stresses, especially red onions that recorded high activities.